Nfix expression critically modulates early B lymphopoiesis and myelopoiesis. - Caitríona O'Connor; Joana Campos; Jason M Osinski; Richard M Gronostajski; Alison M Michie; Karen Keeshan (PLoS ONE)
The commitment of stem and progenitor cells toward specific hematopoietic lineages is tightly controlled by a number of transcription factors that regulate differentiation programs via the expression of lineage restricting genes. Nuclear factor one (NFI) transcription factors are important in regulating hematopoiesis and here we report an important physiological role of NFIX in B- and myeloid lineage commitment and differentiation. We demonstrate that NFIX acts as a regulator of lineage specification in the haematopoietic system and the expression of Nfix was transcriptionally downregulated as B cells commit and differentiate, whilst maintained in myeloid progenitor cells. Ectopic Nfix expression in vivo blocked early B cell development stage, coincident with the stage of its downregulation. Furthermore, loss of Nfix resulted in the perturbation of myeloid and lymphoid cell differentiation, and a skewing of gene expression involved in lineage fate determination. Nfix was able to promote myeloid differentiation of total bone marrow cells under B cell specific culture conditions but not when expressed in the hematopoietic stem cell (HSPC), consistent with its role in HSPC survival. The lineage choice determined by Nfix correlated with transcriptional changes in a number of genes, such as E2A, C/EBP, and Id genes. These data highlight a novel and critical role for NFIX transcription factor in hematopoiesis and in lineage specification.